Study of the adaptive capabilities of the functional state of the basketball players’ organism to physical loads during the microcycle of the preparatory training period - Корсун, Світлана; Шапошнікова, Ірина; Помещикова, Ірина (Slobozhanskyi Herald of Science and Sport, 2018)
Svitlana Korsun, Iryna Shaposhnikova & Iryna Pomeshchikova Purpose: to determine the adaptive capabilities of the functional state of the organism of young basketball players to physical loads during the training microcycle of the preparatory period. Material & Methods: in the study involved 10 basketball players of 14–15 years of training and training group of children’s and youth sports school in Kharkov. The survey was conducted during the microcycle of the preparatory period and 12 months later in the preparatory period at the stage of special training. To assess the adaptive capabilities of the functional state of basketball players, a cyto-biophysical method for determining the bioelectrical properties of the nuclei of buccal epithelial cells. Results: the research of the functional state of the basketball players organism on the index of electronegativity (EN%) of the buccal epithelial cell nuclei after exposure to physical loads of various directions showed that the proposed physical loads during the training process proved to be quite effective for the development of athletes preparedness, as evidenced by the improvement in the adaptive capabilities of the basketball players’ organism during the considered period of sports training. Conclusions: electronegativity index (EN%) of the buccal epithelial cell nuclei in basketball players after the action of physical loads at the end of the microcycle does not change reliably, but has only a tendency to decrease, which indicates a favorable course of the athlete’s organism adaptation processes to physical loads and the rational construction of the microcycle training program.